An Important Finding of White Matter Injury in Late Preterm Infant: Deep Medullary Vein Involvement - Chen, Dan; Sun, Jing; Li, Qiuyu; Bai, Wenjuan; Mao, Jian (Frontiers in Pediatrics, 2020)
Objective: To investigate high risk factors and magnetic resonance imaging (MRI) features in late preterm infants with severe white matter injury (WMI) associated with abnormal deep medullary veins (DMVs). Materials and methods: Preterm infants with severe WMI, who were hospitalized in Shengjing Hospital from 1st January 2009 to 31st December 2018, were enrolled in this retrospective study. High risk factors and MRI characteristics of infants with abnormal DMVs were analyzed and compared with those of infants without DMV abnormalities. Results: A total of 2032 late preterm infants were examined by MRI; 71 cases (3.5%) had severe WMI and 15 of these (21.1%) had abnormal DMVs. The incidence of maternal diabetes was higher in infants with abnormal DMVs and neonatal convulsions were more likely (P < 0.05). The incidence of grade Ⅳ injury (P < 0.05), white matter periventricular cysts and thalamic injury (P < 0.01), cerebral venous sinus thrombus (P < 0.01) and germinal matrix/intraventricular hemorrhage (P < 0.05) were higher in infants with abnormal DMVs than in infants with normal DMVs. Conclusions: Congestion/thrombosis of DMVs may be an important cause of severe WMI in late preterm infants, especially in periventricular leukomalacia-like WMI. WMI with abnormal DMVs is more likely to lead to thalamic injury.